TRADEMARK GUDANG GARAM VERSUS GUDANG BARU - Saputra, Angga (PT. Altin Riset Publishing, 2023)
The purpose of this study is to analyze the issue of trademark rights disputes between Gudang Garam and Gudang Baru regarding the name and logo of a painting or picture. The dispute is related to the brand name and the painting displayed on the New Warehouse product. The approach used in this study is qualitative, with case studies being the method used by researchers. The things that will be examined in this research are related to the trademark dispute rights regulation between Gudang Garam and Gudang Baru and both the content and legal considerations of the judges in the trademark dispute rights case between Gudang Garam and Gudang Baru. Researchers in this study will specifically examine the issue of trademark rights between Gudang Garam and Gudang Baru. This study employs normative legal methods and data collection, as well as a literary or conceptual approach. This research on analyzing research data was carried out using the case study method. The results of the study stated that the New Warehouse had violated the provisions regarding trademark registration in accordance with Article 1 Paragraph (1) of the Law on Trademarks and Geographical Indications N 20 of 2016 and Article 18 Paragraph (3) of the Regulation of the Minister of Law and Human Rights No. 67 of 2016 concerning Trademark Registration related to the brand name and the Gudang Garam painting, which is referred to as a well-known brand.